2001
DOI: 10.1038/35099674
|View full text |Cite
|
Sign up to set email alerts
|

Developmental arrest in vent worm embryos

Abstract: Temperature is a key factor in controlling the distribution of marine organisms and is particularly important at hydrothermal vents, where steep thermal gradients are present over a scale of centimetres. The thermophilic worm Alvinella pompejana, which is found at the vents of the East Pacific Rise (2,500-m depth), has an unusually broad thermotolerance (20-80 degrees C) as an adult, but we show here that the temperature range required by the developing embryo is very different from that tolerated by adults. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
72
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 6 publications
4
72
0
Order By: Relevance
“…At the end of 45 days' cultivation the nauplii still contained considerable lipid reserves, indicating the likelihood of more developmental stages and a potential for long distance dispersal. There is a possibility the nauplii could remain relatively dormant at near-bottom temperatures, 2.5 to 3.08C in the New Ireland and Manus Basins (Gamo et al, 1993;Herzig & Hannington,1994), to be activated into faster growth and metamorphosis to the cyprid stage on encountering suitable environmental signals at vents or seeps (Pradillon et al, 2001). The lipid reserves may make the larvae buoyant, as observed at the surface, but lipid buoyancy changes under pressure (Yayanos et al, 1978) and the nauplii might remain demersal at the depths where the adults live.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of 45 days' cultivation the nauplii still contained considerable lipid reserves, indicating the likelihood of more developmental stages and a potential for long distance dispersal. There is a possibility the nauplii could remain relatively dormant at near-bottom temperatures, 2.5 to 3.08C in the New Ireland and Manus Basins (Gamo et al, 1993;Herzig & Hannington,1994), to be activated into faster growth and metamorphosis to the cyprid stage on encountering suitable environmental signals at vents or seeps (Pradillon et al, 2001). The lipid reserves may make the larvae buoyant, as observed at the surface, but lipid buoyancy changes under pressure (Yayanos et al, 1978) and the nauplii might remain demersal at the depths where the adults live.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary experiments with in vitro fertilisation of A. pompejana suggested that embryos arrest development at low abyssal temperature (2°C), but resume development when temperature increases to 10°C (Pradillon et al, 2001). However, they were unable to develop when the temperature is above 20°C.…”
mentioning
confidence: 99%
“…These results suggested that embryos must develop at intermediate temperatures, lower than in the adult habitat, where temperatures around or above 20°C have been reported (Cary et al, 1998;Chevaldonné et al, 1992;Desbruyères et al, 1985), but higher than the surrounding abyssal sea. Pradillon et al (2001) proposed that embryos could either develop at the bottoms of chimneys where intermediate temperatures are found, or be carried in an arrested state far from their places of origin, completing development only when warmer habitats are encountered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For alvinellids, direct benthic development has been suggested (Desbruyères & Laubier 1986, Zal et al 1995. However, for Alvinella pompejana, experimental studies of its development rather suggest that embryos would develop away from adult colonies, and possibly undergo a dispersal phase (Pradillon et al 2001). Reproductive mechanisms also remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%